Beyond partying characterizing the LGBTQ movement in the Philippines - Evangelista, John Andrew G. (2018)
Access online through this link: https://journals.upd.edu.ph/index.php/pssr/article/view/7914/6902
Keywords: Social movements; LGBTQ+ people; LGBTQ+ activists; LGBTQ+ pride parades